Isolation and antioxidant activity of 5-methyldihydroflavasperone from ethanol leaf extract of Guiera senegalensis JF Gmel - Mosa E.O. Ahmed; Jeremiah Senabe; Ewura S. Yahaya; Gerda Fouche; Paul Steenkamp; Vanessa Steenkamp (AOSIS, 2022)
Background: Guiera senegalensis (Ghibaish) is a medicinal plant extensively used in central and west Africa for the management of various diseases. Aim: This study aimed to determine the antioxidant activity of the ethanol leaf extract of the plant. Method: The ethanol leaf extract was sequentially sub-fractionated using liquid-liquid extraction, vacuum-liquid chromatography and preparative thin layer chromatography. Ultra-performance liquid chromatography with accurate mass spectrometry and nuclear magnetic resonance were employed to isolate and confirm the identity of the most abundant compound. The antioxidant activity of the fractions and isolated compound was assessed by bioautography analysis and the 2,2-diphenyl-1-picrylhydrazyl hydrate (DPPH) radical scavenging assay. Results: The dichloromethane subfraction contained the most promising antioxidant activity (IC50 = 3.18 µg/mL). Purification of this subfraction led to the isolation of a brown crystalline compound, which was identified as 5-methyldihydroflavasperone (IC50 4000 µg/mL). Conclusion: This is the first report of the isolation of 5-methyldihydroflavasperone from the ethanol leaf extracts of G. senegalensis. This compound was not found to be responsible for the antioxidant activity observed. Further research is warranted to identify the compound responsible for the antioxidant activity.